A NEW MULTI-MODAL BIOMETRIC SYSTEM BASED ON FINGERPRINT AND FINGER VEIN RECOGNITION - AHMED, NAVEED (Fırat Üniveristesi, 2014)
In this thesis it has been proposed a system which is based on fusion of fingerprints and finger vein patterns. Both techniques are old and already in use, difference is this in proposed system the same processing steps have been used for fingerprint and finger vein pattern images so it is not required to have two different kinds of software for handling two different kinds of images and fortunately results are more accurate than expected. Fingerprints have lines in the language of biometric they are called ridges. Where these lines (ridges) end they are called termination points where these lines divide into two branches they are named bifurcation points. These points are actually main features their unique positions in the image of fingerprint help to differentiate between two fingerprint images. Same technique has been used for finger vein pattern. Finger veins appear same as ridges in the image and have same features It means veins also have termination points and bifurcation points. In proposed system both kinds of images have been prcocessed by using same steps with the help of MATLAB software then compared them with previously stored images and calculated some scores. These scores are actually number of matched points in both images. In last phase a final score has been calculated for decision that final score is actually an average of previously calculated fingerprint and finger vein pattern scores. Results have proved the ability of the proposed system. Secondly it is multi-modal system so its accuracy and security level is much better than uni-modal systems. Input comes from two different sources and one of the source (finger vein pattern) is not very easy to alter or it can be said like that it is near to impossible. Equipment is also not very expensive or sensitive plus there is not any hesitation factor for users.

In this thesis it has been proposed a system which is based on fusion of fingerprints and finger vein patterns. Both techniques are old and already in use, difference is this in proposed system the same processing steps have been used for fingerprint and finger vein pattern images so it is not required to have two different kinds of software for handling two different kinds of images and fortunately results are more accurate than expected. Fingerprints have lines in the language of biometric they are called ridges. Where these lines (ridges) end they are called termination points where these lines divide into two branches they are named bifurcation points. These points are actually main features their unique positions in the image of fingerprint help to differentiate between two fingerprint images. Same technique has been used for finger vein pattern. Finger veins appear same as ridges in the image and have same features It means veins also have termination points and bifurcation points. In proposed system both kinds of images have been prcocessed by using same steps with the help of MATLAB software then compared them with previously stored images and calculated some scores. These scores are actually number of matched points in both images. In last phase a final score has been calculated for decision that final score is actually an average of previously calculated fingerprint and finger vein pattern scores. Results have proved the ability of the proposed system. Secondly it is multi-modal system so its accuracy and security level is much better than uni-modal systems. Input comes from two different sources and one of the source (finger vein pattern) is not very easy to alter or it can be said like that it is near to impossible. Equipment is also not very expensive or sensitive plus there is not any hesitation factor for users.
Parmak izi ve parmak damar tanımaya dayalı yeni bir çoklu model biometrik sistem
Keywords: Bilgisayar Mühendisliği Bilimleri-Bilgisayar ve Kontrol